OFFICE DOCUMENTATION OF MILITARY-ADMINISTRATIVE INSTITUTIONS AS A SOURCE FOR THE STUDY OF MILITARY RECRUITMENT OF THE JEWISH POPULATION OF VOLYN PROVINCE IN THE XIX CENTURY (Південний архів (історичні науки), 2022)
Purpose. The article is devoted to the source analysis of business documents on the history of the recruitment of the Jewish population of Volyn in the XIX century. To achieve the goal general scientific, historical and source study methods of research are used in the work. Results. The study analyses the official set of documents stored in the Central State Historical Archive of Ukraine, the State Archives of Volyn, Zhytomyr regions. These are orders, directives, journals and minutes of meetings, reports, reports, acts and materials of various commissions, appeals, official correspondence and other information and reference documents of institutions, etc., certifying the use of recruitment by the Russian imperial authorities as a mechanism for assimilation of different ethnic groups including Jewish. These are orders, instructions, journals and proceedings, accounts, reports, acts and materials of various commissions, appeals, official correspondence and other information and reference documentation of institutions, etc. They testify to the use of recruitment by the Russian imperial authorities as a mechanism for the assimilation of representatives of different ethnic groups, including the Jewish one. The information potential of the researched sources concerning coverage of the following issues is defined: legal and organizational support of conscription; features of recruitment by the Jewish population both in the national and regional aspects; the place and functions of central, regional and local authorities in the recruitment of Jews. Conclusions. According to the documents of the state archives of Ukraine, it is possible to trace the entire course of preparation and conduct of recruitment among various social and ethnic groups in general in the Russian Empire, as well as in some recruitment stations in the Volyn province. Documents of recruiting presences, the Offices of the Governor- General of Kyiv, Podolsk and Volyn allow us to fully cover the process of conscription by the Jewish population of Volyn and compare it with the military service of other ethnic groups in the province. They are also an important source for determining the effects of the military factor on the demographic, social, economic, religious and psychological situation of Jewish communities in the XIX century and confirm the aggressive and violent assimilation policy of the Russian autocracy.
Keywords: document, source, state archives, conscription, recruitment, Jewish community, Volyn province.